The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1101/gad.285312.116
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-specific demethylase 1 promotes brown adipose tissue thermogenesis via repressing glucocorticoid activation

Abstract: Brown adipocytes display phenotypic plasticity, as they can switch between the active states of fatty acid oxidation and energy dissipation versus a more dormant state. Cold exposure or β-adrenergic stimulation favors the active thermogenic state, whereas sympathetic denervation or glucocorticoid administration promotes more lipid accumulation. Our understanding of the molecular mechanisms underlying these switches is incomplete. Here we found that LSD1 (lysine-specific demethylase 1), a histone demethylase, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 36 publications
3
76
0
Order By: Relevance
“…Studies by Sambeat et al (2016) demonstrated that LSD1 interacts with Zfp516 to activate UCP1 and other BAT genes. Similar to the work of Zeng et al (2016), Sambeat et al (2016) showed that LSD1 ablation in brown fat resulted in impaired BAT development, increased fat mass, and decreased energy expenditure. A previous report demonstrated that Zfp516 interacts with PRDM16, suggesting that LSD1 forms a transcriptional complex to demethylate H3K9 (Dempersmier et al 2015).…”
supporting
confidence: 63%
See 4 more Smart Citations
“…Studies by Sambeat et al (2016) demonstrated that LSD1 interacts with Zfp516 to activate UCP1 and other BAT genes. Similar to the work of Zeng et al (2016), Sambeat et al (2016) showed that LSD1 ablation in brown fat resulted in impaired BAT development, increased fat mass, and decreased energy expenditure. A previous report demonstrated that Zfp516 interacts with PRDM16, suggesting that LSD1 forms a transcriptional complex to demethylate H3K9 (Dempersmier et al 2015).…”
supporting
confidence: 63%
“…In this issue of Genes & Development, Zeng andcolleagues (pp. 1822-1836) identify lysine-specific demethylase 1 (LSD1) as a pivotal regulator of whole-body energy expenditure by controlling the oxidative and thermogenic activity of brown adipose tissue (BAT).…”
mentioning
confidence: 99%
See 3 more Smart Citations